Определение величины перемещения пьезопривода форсунки - Стрелец, А.А. (Електротехніка і електромеханіка, 2011)
A problem of an injector piezoelectric actuator displacement determination through output signal amplitude is considered. The output signal amplitude is determined via experimental research. Functional dependence of the piezoelectric actuator piezoelectric element displacement on the output signal amplitude is revealed.